Asian regional workshop on environmental training of practising civil engineers : final report, 12-23 May 1975, Faculty of Engineering, University of Malaya, Kuala Lumpur - Asian Regional Workshop on Environmental Training of Practising Civil Engineers (1975 : Kuala Lumpur) ([Kuala Lumpur] : [UNESCO/United Nations])
10